230k views
4 votes
Factories completely

\frac{x {2}^{} }{4y {}^(2 ) } - (1)/(9)


User Cyboashu
by
6.3k points

2 Answers

0 votes

Answer:

(x/2y + 1/3)(x/2y - 1/3).

Explanation:

x^2/4y^2 - 1/9.

This is the difference of 2 squares:

The square root of x^2/4y^2 = x / 2y and square root of 1/9 is 1/3.

So we have:

x^2/4y^2 - 1/9

= (x/2y + 1/3)(x/2y - 1/3).

User Deanie
by
6.2k points
2 votes

Answer:

see explanation

Explanation:

This is a difference of squares and factors in general as

a² - b² = (a - b)(a + b)


(x^2)/(4y^2) = (
(x)/(2y) )² ⇒ a =
(x)/(2y)


(1)/(9) = (
(1)/(3) )² ⇒ b =
(1)/(3)

Hence


(x^2)/(4y^2) -
(1)/(9)

= (
(x)/(2y) )² - (
(1)/(3)

= (
(x)/(2y) -
(1)/(3) )(
(x)/(2y) +
(1)/(3) )

User Mustapha GHLISSI
by
5.7k points